2013
DOI: 10.3109/09553002.2013.756595
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of low-dose radiation from computed tomography scanning

Abstract: Although the LDR effects of CT are still controversial, the current problems include the high frequency-use and abuse of CT scans, the increase of radiation dose and accumulative dose in high-accuracy CT, and the poor understanding of carcinogenic risks. The underlying biological basis needs further exploring and the ratio of risks and benefits should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Breast cancer was also expected to be higher in HHT patients: As for any discipline in which screening and treatment modalities include exposure to ionising radiation, there are discussions about the degree to which health benefits may be offset by an increase in cancer rates [57-61]. In HHT, this is particularly true for brain, lung and breast tissues which lie within the radiation exposure fields for CT scans and angiographic studies that are essential to treat HHT cerebral and pulmonary AVMs respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer was also expected to be higher in HHT patients: As for any discipline in which screening and treatment modalities include exposure to ionising radiation, there are discussions about the degree to which health benefits may be offset by an increase in cancer rates [57-61]. In HHT, this is particularly true for brain, lung and breast tissues which lie within the radiation exposure fields for CT scans and angiographic studies that are essential to treat HHT cerebral and pulmonary AVMs respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CT scanning provides more thorough diagnostic details than X-ray but at the cost of patient exposure to a higher radiation dose, estimated at 15-30 mGy (compared with 0.01-0.15 mGy from X-ray imaging) (47). Cumulative CT-related low-dose IR has been correlated with detrimental biological effects such as DNA damage, bystander effects, tissue injury, and, in some cases, carcinogenesis (218). The biological consequences of low-dose IR have been recently reviewed (218), and illustrate that although CT is a valuable diagnostic tool, excessive exposure, especially in children, may lead to cancer and should be limited (241,263).…”
Section: Fundamentalsmentioning
confidence: 99%
“…Radioadaptive dosing, where cells are pre-primed with a low dose, can reduce vulnerability to subsequent exposure to higher doses, also producing a neuroprotective effect. Otsuka et al [123] demonstrated that animals primed with pre-exposure to doses of 0.5 Gy gamma radiation developed increased resistance to DNA damage after subsequent exposure to a higher challenge dose of 1.6 Gy, compared to mice irradiated with the higher dose alone [123], indicative of a radioadaptive response [22], [124]. In terms of inflammation, decreases in pro-inflammatory markers in the mouse hippocampus and cortex were present only in animals primed with a 0.1 Gy dose prior to subsequent exposure to 2 Gy, suggesting that early exposure to low doses can prevent the upregulation of inflammation by higher doses [100].…”
Section: The Impact Of Low Dose Ionising Radiation On the Cnsmentioning
confidence: 99%
“…Mitochondrial redox balance and microglial responses are also critical in modulating responses to low dose irradiation, largely through the stimulation of antioxidant defences [7]. Whilst some evidence still points to a linear dose-response pattern, there is significant evidence to suggest that lower doses can confer protection to cell functioning, molecular structures, synapses, and key brain mechanisms such as neurogenesis, and induce reparative mechanisms in the face of CNS pathology [10], [22]. Based on guidelines by regulatory bodies, as well as data generated by low dose radiation research programs, a low dose is considered to be acute exposure to less than 100mSv, or 0.1 Gy [23], [24].…”
Section: Introductionmentioning
confidence: 99%